Displaying 31RG-1 peptide on the surface of HPV16 L1 by use of a human papillomavirus chimeric virus-like particle induces cross-neutralizing antibody responses in mice - Xue Chen; Ting Zhang; Hongyang Liu; Yaru Hao; Guoyang Liao; Xuemei Xu (Taylor & Francis Group, 2018)
Current available human papillomavirus (HPV) vaccines are based on the major capsid protein L1 virus-like particles (VLPs), which mainly induce type-specific neutralizing antibodies against vaccine types. Continuing to add more types of VLPs in a vaccine raises the complexity and cost of production which remains the principal impediment to achieve broad implementation of HPV vaccines, particularly in developing regions. In this study, we constructed 16L1-31L2 chimeric VLP (cVLP) by displaying HPV31 L2 aa.17-38 on the h4 coil surface region of HPV16 L1, and assessed its immunogenicity in mouse model. We found that the cVLP adjuvanted with alum plus monophosphoryl lipid A could induce cross-neutralizing antibody responses against 16 out of 17 tested HPV pseudoviruses, and the titer against HPV16 was as high as that was induced by HPV16 L1VLP (titer > 105), more importantly, titers over 103 were observed against two HR-HPVs including HPV31 (titer, 2,200) and −59 (titer, 1,013), among which HPV59 was not covered by Gardasil-9, and medium or low titers of cross-neutralizing antibodies against other 13 tested HPV pseudoviruses were also observed. Our data demonstrate that 16L1-31L2 cVLP is a promising candidate for the formulation of broader spectrum HPV vaccines.